Effect of Dietary 1, 25-Dihydroxycholecalciferol Concentration on Growth Performance and Bone Characteristics of Japanese Quail Fed Diet Deficient in Calcium and Phosphorus - Sheikhlar, A.; Navid, S. (Pakistan Journal of Nutrition, 2009)
An investigation was carried out to assay the concentration of dietary 1, 25-dihydroxycholecalciferol [1, 25(OH)2D3] on growth parameters and bone characteristics includes bone ash, Tibial Dyschondroplasia (TD) incidence and plasma minerals in broiler quails. Diets comprised control diet (diet 1) with sub optimal levels of calcium (0.71%) and total phosphorus (0.37%) and diets 2, 3, 4 and 5 that contained control diet supplemented with 2.5, 4.5, 6.5 or 8.5 μg/Kg 1,25(OH)2D3. Dietary treatments had no effect (p>0.05) on the live weight gain and feed conversion ratio. Bone ash was increased significantly (p